Profilaxia da transmissão vertical do HIV: compreensão do vivido do ser-casal e possibilidades de cuidado - Langendorf, Tassiane Ferreira (2012)
The aim was to unveil the meaning of being-a-couple on the lived experience on prophylaxis of HIV vertical transmission. Qualitative and phenomenological inquiry based on theoreticalphilosophical- methodological referential of Martin Heidegger. Subjects of research were couples being health monitored in the Ambulatory of infectious Diseases on pre-natal and childcare of University Hospital of Santa Maria. Data production happened between December 2011 to February 2012 through phenomenological interview, with seven couples. It was developed heideggerian analysis, unveiling that on vague and median comprehension of the couple who experiences of prophylaxis of HIV vertical transmission with health care meaning making everything right since pre-natal care, taking medicine and going to consults, not breast-feeding and giving medicine to the child; not imagining that could be infected, not having guarantee of treatment working and being scared of transmitting HIV to the child; considering that not breast-feeding is sad, new and mourning to the women that doesn t stop being a mother, but it s not complete and that in front of others it s complicated for the couple not to breast-feed. Given this experience, couple is together and takes care of each other, continue to have a normal life, as if they didn t have the disease, however prejudice make them silent about their diagnosis. The couple takes care of the child to be healthy and is involved with him/her. With the child, they become a family and not only a couple. On interpretative comprehension, the woman and the partner show themselves as being-a-couple that is occupied in developing the treatment for prophylaxis. It s on the talk repeating information about care, curious on search for knowledge to simply become conscious about the disease and treatment and ambiguous when states having a normal life in spite of the difference in taking medicines and using condoms. It reveals itself in the decadence. They were afraid of the treatment did not work, were surprised on the facticity of being unable to breastfeed, and fell in front of the impersonality prejudice and discrimination. It has been shown to be as-family. The couple lived in be-revealed that the gain in the prophylaxis of stress as the child has health and family formation. They pointed to the importance of including the partner in care and reproductive care in childcare. Sees the need to promote attention the relationship between being professional and be double that transcends the impersonal dictates what the being-a-couple should be engaged in.